(untitled) (Bangladesh Journal of Medical Science, 2020)
Objectives: The aim of this study is to evaluate the factors affecting subjective symptoms, especially pain and swelling in submandibular gland sialolithiasis. Methods: We analyzed the computed tomographic (CT) findings of submandibular gland sialolithiasis (stone size/location/ number) and assessed white blood cell (WBC) (neutrophil/absolute neutrophil count) and erythrocyte sedimentation rate (ESR) to elucidate the correlation with subjective symptoms, especially swelling and pain. Results: Of the 82 patients, 45had a solitary stone. Thirty seven patients experienced pain and 73 patients had swelling. The number, location and size of the calculi were not associated with symptoms, especially pain and swelling. From logistic regression analysis, WBC (p=0.048) and the percentage of neutrophils (p=0.027) were associated with the presence of pain, but not swelling. Conclusion: To our knowledge, this is the first study to observe that both the location and size of stone are not significantly related to subjective symptoms, especially pain and swelling in submandibular gland sialolithiasis. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.240-244